1991
DOI: 10.1007/bf00152649
|View full text |Cite
|
Sign up to set email alerts
|

Electric currents and H? emission in two active regions on the sun

Abstract: We investigated the structure of magnetic field and vertical electric currents in two active regions through a comparison of the observed transverse field with the potential field, which was computed according to Neumann boundary-value problem for the Laplace equation using the observed H:-value. Electric currents were calculated from the observations of the transverse magnetic field.There exist two systems of vertical electric currents in active regions: a system of local currents and a global one. The global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 4 publications
1
10
0
1
Order By: Relevance
“…For example, based on 18 years of observations, Zirin & Liggett (1987) found that sunspots are responsible for almost all great flares. Temporal and spatial correspondence between the magnetic topological properties of active regions and solar flares have been reported, supporting the idea that the presence of strong electric current systems contributes to the flare activity (Moreton & Severny 1968;Abramenko et al 1991;Leka et al 1993;Wang et al 1994Wang et al , 1996Wang et al , 2006Tian et al 2002, etc.). Falconer (2001) and Falconer et al (2003) measured the lengths of strong-sheared and strong-gradient magnetic neutral line segments, respectively, and found that they are strongly correlated with each other and both might be prospective predictors of the CME productivity of active regions.…”
Section: Introductionsupporting
confidence: 54%
“…For example, based on 18 years of observations, Zirin & Liggett (1987) found that sunspots are responsible for almost all great flares. Temporal and spatial correspondence between the magnetic topological properties of active regions and solar flares have been reported, supporting the idea that the presence of strong electric current systems contributes to the flare activity (Moreton & Severny 1968;Abramenko et al 1991;Leka et al 1993;Wang et al 1994Wang et al , 1996Wang et al , 2006Tian et al 2002, etc.). Falconer (2001) and Falconer et al (2003) measured the lengths of strong-sheared and strong-gradient magnetic neutral line segments, respectively, and found that they are strongly correlated with each other and both might be prospective predictors of the CME productivity of active regions.…”
Section: Introductionsupporting
confidence: 54%
“…It is known from direct calculations based on vector-magnetograms that electric currents are ubiquitous in ARs (see, e.g., Abramenko et al 1991;Leka et al 1993Leka et al , 1996Pevtsov et al 1994;Abramenko et al 1996;Wheatland 2000;Zhang 2002;Schrijver et al 2005;Leka & Barnes 2007;Schrijver et al 2008;Schrijver 2009). We found here that photospheric magnetic fields are in a state of under-developed turbulence when both the energy cascade and energy dissipation at all scales are present in the system.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…To date, various observational studies have explored the connection between photospheric magnetic fields and solar flares, supporting the hypothesis that solar flares are driven by the nonpotentiality of magnetic fields (Moreton and Severny, 1968;Abramenko, Gopasyuk, and Ogir', 1991;Leka et al, 1993;Wang, Xu, and Zhang, 1994;Wang et al, 1996;Tian, Liu, and Wang, 2002;Abramenko, 2005). Through five solar flares, found there are obvious changes of the magnetic gradient occurring immediately and rapidly following the onset of each flare.…”
Section: Introductionmentioning
confidence: 76%
“…The overall flare productivity of a given active region, which is quantified by weighting the soft X-ray (SXR) flares of X-, M-, C-and B-class as 100, 10, 1, and 0.1, respectively (Antalova, 1996;Abramenko, 2005), is given by…”
Section: Definition Of the Predictive And Response Variablesmentioning
confidence: 99%